Adipose Tissue-Derived Mesenchymal Stem Cells Induce Expansion of Interleukin-10-Producing Regulatory B Cells and Ameliorate Autoimmunity in a Murine Model of Systemic Lupus Erythematosus. Issue 11 (November 2015) - Park, Min-Jung; Kwok, Seung-Ki; Lee, Sung-Hee; Kim, Eun-Kyung; Park, Sung-Hwan; Cho, Mi-La
Mesenchymal stem cells (MSCs) are multipotent cells characterized by immunomodulatory properties and are therefore considered a promising tool for the treatment of autoimmune diseases. One functional B-cell subset, regulatory B cells (Bregs), has recently been shown to restrain excessive inflammatory responses in autoimmune diseases. In the present study, we investigated the impact of human adipose-derived MSCs on Bregs and their therapeutic effect in an animal model of systemic lupus erythematosus (SLE). Coculture of human adipose-derived MSCs with splenocytes from C57BL/6 mice expanded the population of interleukin-10-producing B cells (B10 B cells). In vivo treatment with human adipose-derived MSCs reduced serum anti-double-stranded antibody levels and improved renal pathology of lupus mice (Roquin san/san mice). MSCs decreased ICOS + CD44 + follicular helper T cells, Th1 cells and Th17 cells, in spleens of Roquin san/san mice. In contrast, MSCs increased Foxp3-expressing regulatory T cells. MSCs also decreased the size and number of germinal centers and effector B cells. As expected, in vivo treatment with MSCs expanded the population of Bregs in spleens of Roquin san/san mice. Our results indicate that human adipose-derived MSCs induce the expansion of Bregs and ameliorate autoimmunity in a murine model of SLE. These findings suggest that human adipose-derived MSCs may be a promising therapeutic strategy targeting B-cell-mediated autoimmune diseases such as SLE.